2007
DOI: 10.1021/nl070157q
|View full text |Cite
|
Sign up to set email alerts
|

The SERS Activity of a Supported Ag Nanocube Strongly Depends on Its Orientation Relative to Laser Polarization

Abstract: Silver nanocubes with sharp or truncated corners were synthesized, deposited on silicon substrates, and functionalized with Raman-active thiols for surface-enhanced Raman scattering (SERS) studies. The use of substrates with registration marks allowed us to correlate the SERS spectra from individual nanocubes to their physical parameters revealed by high-resolution SEM imaging. We observed dramatic variations in SERS intensity when the nanocubes were oriented at different angles relative to the polarization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
307
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 333 publications
(321 citation statements)
references
References 43 publications
10
307
0
3
Order By: Relevance
“…For the cube tag, we found that the 4-MBA signal from a cube orientated with a side diagonal axis parallel to the laser polarization was about two times higher than the configuration when the cube was oriented with one of the edges parallel to the laser polarization. This observation is consistent with the results for Ag nanocubes obtained in our previous work [42]. It can be concluded that the intensities of 4-MBA signals from individual tags supported on glass slides decreased in the order of dimer tag ( parallel) ) cube tag ðdiagonalÞ .…”
Section: Surface-enhanced Raman Scattering Properties Of the Dimer Tagsupporting
confidence: 92%
See 1 more Smart Citation
“…For the cube tag, we found that the 4-MBA signal from a cube orientated with a side diagonal axis parallel to the laser polarization was about two times higher than the configuration when the cube was oriented with one of the edges parallel to the laser polarization. This observation is consistent with the results for Ag nanocubes obtained in our previous work [42]. It can be concluded that the intensities of 4-MBA signals from individual tags supported on glass slides decreased in the order of dimer tag ( parallel) ) cube tag ðdiagonalÞ .…”
Section: Surface-enhanced Raman Scattering Properties Of the Dimer Tagsupporting
confidence: 92%
“…Therefore, it should give the strongest SERS signals. Hot spots could also be created at the corner sites of a cubic core of the cube tags [42,46], leading to a higher EF than the sphere tags with spherical cores. Because the three types of tags had a similar major LSPR peak (figure 2d ), the possibility of wavelength-dependent enhancement [43], where the SERS activity is maximized when the excitation source matched the LSPR peak of the tags, could be neglected.…”
Section: Surface-enhanced Raman Scattering Properties Of the Dimer Tagmentioning
confidence: 99%
“…Because of the anisotropic structure of the GNRs, two plasmon resonance bands are induced by the transverse and longitudinal oscillations of free electrons 29 . Note that the SERS intensities depend strongly on both the orientation of the GNRs and the illumination direction of the laser 18,28,30 . When the long axis of the GNRs is perpendicular to the illumination direction of the incident light, a resonance condition in a far-field regime is satisfied resulting in significant amplification of the Raman signal ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[7] The strong dependence on laser polarization could be attributed to the difference in the electric field enhancements under different excitation directions. [15] When comparing the EF of a dimer and that of a single sphere, we found that the EF of an individual sphere was much lower than that of the corresponding dimer, indicating the hotspot phenomenon. Besides, the EF (1.7×10 8 ) for a dimer of 80-nm spheres with the laser polarization parallel to the dimer's long axis is almost ten times higher than that of the dimer of 30-nm spheres.…”
mentioning
confidence: 87%